Is There Insider Trading? An Examination of Merger and Acquisition Announcements in the Indonesian Stock Market - BAMBANG Riyanto L.S.; SUMIYANA SUMIYANA (The Indonesian Journal of Accounting Research, 2013)
This research examines whether domestic investors reacted to merger and acquisition announcements earlier than the foreign investors. Compared to foreign investors, domestic investors are more familiar with the market environment and have more access to information about companies (i.e., there is information leakage). The domestic investors take this informational advantage by initiating trading activities before the information is made public. The foreign investors react to the announcement when such information is officially announced by companies, and some time they do not react immediately. This so-called insider trading phenomenon commonly happens in emerging markets. Two proxies of market reactions were used: abnormal returns and trading volumes.Fifty-four M&A announcements were identified in the Jakarta Stock Exchange from 1999-2006. The price movements and trading activities of each of these two types of investors were analyzed thoroughly during the ninety-one day window test. The findings indicate that no abnormal returns and abnormal trading volumes were observed in the 91 days surrounding the announcement dates. Further analysis, however, shows that there was information leakage for domestic investors. It is further argued that information leakage exists; domestic investors reacted to the M&A information before companies announced that information to the public.